SMALL CLAIM COURT DALAM SISTEM PERADILAN PERDATA DI INDONESIA DAN PELUANG PENERAPANNYA DALAM PENYELESAIAN SENGKETA EKONONOMI SYARI’AH PADA PERADILAN AGAMA - Bustamar, Bustamar (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
The enactment of Small claims court mechanism that marked with the enactment of PERMA Number. 2 Year 2015 concerning Procedure for Simple Quarrel Settlement is a new breakthrough in the civil justice system in Indonesia. This breakthrough was reached by the Supreme Court in order to reduce the queues for settling of civil Quarrel in court that the value is under 200 million. Implementation of Quarrel resolution by Small claim court mechanisms is done by a single judge assisted by a Registrar and can be completed within 25 working days and the decision is final and binding so that it is unable filed an appeal or judicial review to the Supreme Court, the decision of which can be directly execute in accordance with the civil judicial mechanisms in general. Small claims court jurisdiction which is set in PERMA No. 2 2015 is the General Courts, considering the Religious Courts are also authorized to settle a civil case with the Shari'ah economic and legal mechanisms of the same event with the civil court of the General Courts, the judicial application of the Small claims court mechanism in Religion Court is also possible and prospective,so that regulatory support as well as PERMA No. 2 of 2015 applied to the Religious Courts is required, especially in the process of sharia economic quarrel resolution.